KOMITMEN, KOMPETENSI, SEMANGAT KERJA DAN KINERJA - Rizkhaini ' (JIANA ( Jurnal Ilmu Administrasi Negara ), 2016)
Commitment, Competence, Morale and Employee Performance. This study aimed to determine the effect of competence and morale commitment to employee performance at Riau Provincial Education Department. The study uses a quantitative approach. The population is all employees of Riau Province Education Department a total of 210 people and a sample of 130 people using the formula slovin. The technique of collecting data using questionnaires. Data were analyzed with regression two predictors. The results showed that the commitment, competence and morale partially and simultaneously influence performance.